The consumer perception about local versus global brands : an exploratory study. - Ng, Eng Chen. (2011)
This study focused on the perception of young Singaporean consumers towards local brands and global brands. A pre-study was done to gain some knowledge on local consumers‟ perception prior to more extensive research. Based on our pre-study, we found that local brands were losing out to global brands due to less favourable perception. In general, local brands were viewed more cheaply, of lower quality and lower fashionability as compared to global brands which were deemed more stylish, better designs and better quality. Furthermore, we also found more abstract associations for global brands and concrete (or functional) associations for local brands.